Analysis of clinical characteristics of 36 cases of extramammary Paget's disease - Meng-lian LI; Di CAO; Yun PAN; Ai-jun CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To evaluate the clinical features of extramammary Paget's disease by retrospectively studying cases. Methods: Statistical analyses were performed on the clinical data of 36 cases of extramammary Paget's disease from January 2013 to December 2018. Results: Extramammary Paget's disease usually occurred in males with a ratio of 3 ∶1.The average age of onset was (65.72±10.41) years and the course of disease ranged from 6 months to 10 years with a mean of 4 years. Single lesions accounted for the majority, and the most common site was the scrotum. The main lesions were erythema and erosion. 60.61% of the patients were misdiagnosed. Immunohistochemistry showed mainly positive for CK7, CEA and EMA.30 cases had no metastasis while 6 cases did.30 patients underwent extended local excision and intraoperative frozen section, and 2 out of them relapsed. Among the 30 surgical cases, 27 patients had a clear resection range most of which were about 1.0 cm and 2.0 cm. The extended resection of 2.0 cm had a relatively higher one-time total excision rate of 90.91%. Conclusions: Extramammary Paget's disease is more common in males and the elders with a high rate of misdiagnosis. Most of the EMPD lesions are single. Primary or secondary can be distinguished by immunohistochemistry. With a slow progression, extramammary Paget's disease can still metastasize. Extended local excision and intraoperative frozen section is the main treatment and 2.0 cm is suggested as the extended resection.